2017
DOI: 10.1155/2017/4272940
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Propolis in Oxidative Stress and Lipid Metabolism: A Randomized Controlled Trial

Abstract: Although there is evidence of the benefits of propolis on human health, the vast majority of studies have been conducted using animal models. The present study includes the chemical characterization and clinical evaluation of the effects of the oral administration of propolis solution on the oxidative status and modulation of lipids in a human population in Talca, Chile. Chemical characterization of propolis, total phenol, flavonoids, and total antioxidant capacity were determined by ORAC. Identification of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 48 publications
6
89
3
5
Order By: Relevance
“…The results of this study were not consistent with those reported in most of studies conducted to investigate the hepatoprotective effects of Propolis [11,12,13,14,32].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study were not consistent with those reported in most of studies conducted to investigate the hepatoprotective effects of Propolis [11,12,13,14,32].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have reported that Propolis plays a protective role in liver. It prevents the development of fatty liver and its related complications, such as cirrhosis, by reducing the total serum cholesterol, triglyceride, LDL and HDL levels [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Data of the present work indicated that oral administration of Prop could protect liver and preserve NO 2and NO 3level from elevation during sepsis induction. These results were in agreement with (Kismet et al, 2008, Enis Yonar et al, 2011, Mujica et al, 2017. In addition, Prop was also indicated to keep GSH content even during sepsis induction, these results were in agreement with Enis Yonar et al 2011, where they showed that, Preoral treatment with Prop attenuated oxidative stress by markedly decreasing MDA level in tissues.…”
Section: Fig (2): the Protective Effect Of Propolis On Liver Tissue supporting
confidence: 88%
“…Moreover, El-Guendouz et al (2017) indicated that in rats given Prop, the livers of rats receiving Prop showed less lipid. Furthermore, Mujica et al, (2017) also, supported the role of Prop in diverse chronic disease, through different mechanisms such as; the increase in high-density lipoproteins-cholesterol, and its antioxidant effect due to enhanced GSH and by decreasing MDA and markers of oxidative stress. Present results pointed out that the treatment of Prop provided protection against liver damage and modulated the toxic effects of sepsis.…”
Section: Fig (2): the Protective Effect Of Propolis On Liver Tissue mentioning
confidence: 79%
“…In another clinical trial, the oral use of a commercial propolis solution for 90 days showed reduced lipid peroxidation and increased concentration of reduced glutathione (GSH) compared with baseline. In addition, there was also an increase in HDL concentration [ 15 ]. In a study with type 2 diabetes mellitus (DM2) patients, the use of propolis increased the plasma concentration of GSH and reduced oxidation markers [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%